11. PREVALENCE AND ASSOCIATED FACTORS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE AMONG THE ELDERLY IN QUANG NINH DISTRICT, QUANG BINH PROVINCE (Vietnam Journal of Community Medicine, 2024)
Objectives:(1) Identify the prevalence of COPD among the elderly of Quang Ninh district, Quang Binh province(2) Examine associated factors of COPD among participantsMethods: This cross sectional study design was carried out among 600 elderly persons in Quang Ninh district, Quang Binh province. Multiple logistic regression was employed to examine factors associated with COPD.Results: The prevalence of COPD was 11.5%. Factors associated with COPD were age, educational level, occupation, degree of smoking, time of exposure to occupational dust, time of exposure to cooking smoke, coal smoke and history of tuberculosisConclusion: COPD was common among the elderly. Strengthening health education to enhance community knowledge of COPD, organizing routine health checkups, and screening for COPD in the elderly to detect and intervene early COPD are urgently needed among the elderly in Vietnam.
Keywords: COPD; Prevalence; associated factors